Functionalization of gelatin films dressings with silver-doped zinc oxide nanoparticles for prevention of bacterial infection and promoting wound repair - Bahaa A. Hemdan; Samar A. El-Kholy; E. S. Shalaby; A. H. Abd-Al-Aleem; Tarek S. Aysha; Mehrez E. El-Naggar (Scientific Reports)
Abstract Gelatin-based films loaded with silver-doped zinc oxide nanoparticles (Ag-doped ZnONPs) were synthesized using the solution casting technique. The analyzed data of Ag-doped ZnONPs reveal their spherical shape with a small size. In our work, three different concentrations of the prepared Ag-doped ZnONPs (0.05 g, 0.1 g, and 0.2 g) were added to GeL solution for the formation of three films (Ag/ZnO 0.05@GeL film, Ag/ZnO 0.1@GeL film, and Ag/ZnO 0.2@GeL). These prepared films were compared with GeL film that prepared without Ag-ZnONPs. The obtained results demonstrated the relatively homogeneous distribution of Ag-ZnONPs on the surface of the prepared films. Besides, this study investigated the antibacterial properties, biocompatibility, and potential applications of Ag/ZnO 0.2@GeL film for wound healing. Ag/ZnO 0.2@GeL film exhibited the highest antibacterial efficacy, with zones of inhibition ranging from 17 to 21 mm against Gram-negative bacteria. Furthermore, this formulation showed a marked ability to inhibit biofilm formation, completely eradicating bacterial biofilm by day 7. In bacterial growth inhibition assays, Ag/ZnO 0.2@GeL reduced bacterial counts by up to 6 log CFU/mL within 210 min. Biocompatibility was assessed using a Microtox® analyzer, with EC50% values exceeding 100 across all time points, confirming the films’ non-toxic nature. These findings suggest that Ag/ZnO@GeL films, particularly Ag/ZnO 0.2@GeL formulation, offer strong antibacterial activity, effective biofilm suppression, and high biocompatibility, highlighting their potential as multifunctional wound dressings for infection control and enhanced wound healing.